2007
DOI: 10.1038/ng1993
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous silencing of T-box transcription factor EOMES leads to microcephaly with polymicrogyria and corpus callosum agenesis

Abstract: Neural progenitor proliferation and migration influence brain size during neurogenesis. We report an autosomal recessive microcephaly syndrome cosegregating with a homozygous balanced translocation between chromosomes 3p and 10q, and we show that a position effect at the breakpoint on chromosome 3 silences the eomesodermin transcript (EOMES), also known as T-box-brain2 (TBR2). Together with the expression pattern of EOMES in the developing human brain, our data suggest that EOMES is involved in neuronal divisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
133
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(139 citation statements)
references
References 14 publications
4
133
1
1
Order By: Relevance
“…In this context most CC fibers developed and crossed the midline but only a fraction of callosal projections displays pathfinding defects. This is in contrast to the observed CC agenesis in humans (Baala et al 2007) and might indicate species-specific differences.…”
Section: Genes and Development 2481contrasting
confidence: 87%
See 1 more Smart Citation
“…In this context most CC fibers developed and crossed the midline but only a fraction of callosal projections displays pathfinding defects. This is in contrast to the observed CC agenesis in humans (Baala et al 2007) and might indicate species-specific differences.…”
Section: Genes and Development 2481contrasting
confidence: 87%
“…Highest Tbr2 expression is detected between E12 and E16 in IPCs coincident with the peak of murine cortical neurogenesis and decays after E17 (Englund et al 2005;Molyneaux et al 2007). In humans a homozygous chromosomal translocation that disrupts Tbr2 expression is associated with microcephaly, polymicrogyria, corpus callosum (CC) agenesis, cognitive deficits, and severe motor delay with hypotonia (Baala et al 2007). In mice Tbr2 is required for development of the trophectoderm and during germ layer formation, leading to embryonic death before onset of neurogenesis (Russ et al 2000;Arnold et al 2008).…”
mentioning
confidence: 99%
“…Eomes (also referred to as Tbr2) belongs to the Tbr1/Eomes/Tbet subfamily of genes (Naiche et al, 2005) that were initially found to play essential roles during trophoblast and mesoderm development in mice (Russ et al, 2000;Strumpf et al, 2005). Eomes is also expressed in the developing central nervous system and has been implicated in the development of the human central nervous system; a homozygous breakpoint mutation in a Moroccan family silences Eomes and leads to microcephaly (Baala et al, 2007). Recent studies have also indicated that Eomes is a component of a pathway that regulates glutamatergic neurogenesis in the cerebral cortex and cerebellum in mouse development (Bulfone et al, 1999;Hevner et al, 2006;Quinn et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The original T-box family members were identified due to their critical role in embryonic development. In fact, several human genetic diseases are associated with diminished T-box protein function, and the homozygous deletion of T-box proteins such as Brachyury, Eomesodermin (Eomes), and Tbx6 results in a lethal embryonic phenotype in mouse systems (5,7,22,25,26,28,29). The importance of the T-box family in hematopoietic cell development has been more recently recognized with the discovery of T-box expressed in T cells (T-bet) in CD4 ϩ T helper 1 (Th1) cells and the subsequent identification of the overlapping expression profile of Eomes in CD8 ϩ T cells (27,33).…”
mentioning
confidence: 99%